Cooperative Model in Language Reasoning: Indonesian Language Teaching Materials in Teacher Training and Education Faculty of Muhammadiyah Sumatera Utara University - Tepu Sitepu (Britain International for Academic Research (BIAR) Publisher, 2019)
The aim of this study is to determine student’s language reasoning of Mathematics Education and Accounting Education in Teaching Training and Education Faculty of Muhammadiyah Sumatera Utara University. The research method used is an experimental method, where Mathematics Education as a control class or without using cooperative models and Accounting Education as a class experiment or use a cooperative learning models. The sample of this study is 65 students consisting of Mathematics Education students as many as 40 students, Accounting Education students as many as 25 students. Research results on Mathematics Education students through tests without using cooperative learning models obtained Mean= 73.50. Research results on Accounting Education through tests after using cooperative learning models obtained Mean= 76.20. Hypothesis tests conducted by statistical test or t test, it is obtained t count = 1.78 and t table = 1.68. Thus, t count is greater than t table, it can be concluded that cooperative models applied to Accounting Education in learning can improve student’s language reasoning.